Eksplorasi Etnomatematika pada Bangunan Keraton Kacirebonan - Sofhya, Herlinda Nurafwa; Az-zahwa, Salma (Universitas Negeri Surabaya, 2024)
This research is an exploration of Philosophical values and Mathematical Concepts in the building design of Kacirebonan Palace. This research was conducted in order to respond to changes in the independent curriculum in accordance with Kepmendikbudristek number 56 of 2022 which requires education units to add local content. Local content can be added through integration with other subjects, through Pancasila profile projects, or stand alone as a subject. The results of the exploration of ethnomathematics in the Kacirebon palace building can be a reference in integrating local content in mathematics subjects. Data collection through interviews with palace servants and relatives of the palace and direct observation at the Kacirebonan palace. Based on the results of the study, most of the philosophical values contained are religious values in accordance with Islamic teachings. This philosophical value is contained in the building structure, layout, building names, and reliefs or carvings on the walls of the palace. The mathematical concepts that exist in the design of the palace buildings are mostly the concept of geommetry, especially the geometry of spaces such as pyramids and prisms, this is illustrated from the roof shape of the palace. In addition to the concept of geometry there are also geometry transformations such as mirroring on most of the palace gates, and the concept of congruence on the window vents of the kacirebonan palace.